2020
DOI: 10.1177/1120672120978355
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of dexamethasone implants following anti-VEGF failure for macular oedema in retinal vein occlusion

Abstract: Purpose: To investigate the efficacy of intravitreal dexamethasone implants (DEX) after anti-VEGF failure in retinal vein occlusion macular oedema. Methods: Retrospective cohort study of DEX implant (0.7 mg) given after anti-VEGF ‘failure’. Switch to DEX occurred if a ⩽ +5 ETDRS letter gain and ⩽20% reduction in central subfield thickness was present following ⩾6 consecutive anti-VEGF injections. The primary endpoint was VA change 30 days after DEX. Secondary outcomes were peak VA change, VA change at monthly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…However, the results of RCTs may not reflect real-world effectiveness, since the actual practices in clinics may differ from the conditions strictly controlled by RCTs. Inadequate or non-standard treatment in clinical practice often leads to unsatisfactory treatment outcomes, requiring additional injections or switching to a different anti-VEGF drug [9][10] or dexamethasone implants (DEX) [11][12] in followup visits. Several retrospective real-world studies [13][14][15] that used 1+PRN or 3+PRN treatment regimens reported mean numbers of injections in the first year of 3.7 to 7.6, and a mean improvement in visual acuity (VA) of 8.0 to 14.8 letters at month 12, indicating that fewer injections in real clinical practices may result in unsatisfied BCVA improvement.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of RCTs may not reflect real-world effectiveness, since the actual practices in clinics may differ from the conditions strictly controlled by RCTs. Inadequate or non-standard treatment in clinical practice often leads to unsatisfactory treatment outcomes, requiring additional injections or switching to a different anti-VEGF drug [9][10] or dexamethasone implants (DEX) [11][12] in followup visits. Several retrospective real-world studies [13][14][15] that used 1+PRN or 3+PRN treatment regimens reported mean numbers of injections in the first year of 3.7 to 7.6, and a mean improvement in visual acuity (VA) of 8.0 to 14.8 letters at month 12, indicating that fewer injections in real clinical practices may result in unsatisfied BCVA improvement.…”
Section: Introductionmentioning
confidence: 99%